Gender Bias & Religious Discrimination: Positive Framing of News Report Coverage on Mauree Turner - Erwanda Resti Chaerunnisa; Aris Munandar (Rubikon : Journal of Transnational American Studies, 2022)
Mass media plays an important role in our lives and society to a greater degree. As a primary source of information that people tend to go for, the kind of information mass media provides matters. The problem is that every message we see in the media is constructed and that even texts like news reports are not entirely authentic. Previous studies have shown that news media do have their own tendency in writing their news reports, through which the minority communities are usually the ones to receive the short end of the stick. On that account, this study, through conducting critical discourse analysis, attempts to see the media framing in Mauree Turner’s 2020 Oklahoma state legislative election news reports and find an underlying motive behind such framing. The finding shows that in general, the media framed Turner positively in their reports and that this positive frame implies an inherent gender bias and religious discrimination within American society.